Improving Students' Metacognitive Awareness and Mathematical Communication Ability with Think Pair Share Learning Model - Muhammad Tusaldi Junian Satrio; Ari Septian; Sarah Inayah (Universitas Suryakancana, 2026)
This study aims to analyze and compare the improvement of students’ metacognitive awareness and mathematical communication ability through the implementation of the Think Pair Share learning model and conventional learning. The research method used is quasi-experimental with a nonequivalent comparison group design. The population of this study consists of all students of class XI at SMK Negeri 1 Cipanas in the academic year 2024/2025. The sample includes class XI MPLB 1 (experimental group) and XI TJKT (control group), selected using purposive sampling technique. The instruments used are a mathematical communication ability test and a metacognitive awareness questionnaire with matrix material. Data analysis was conducted using normality test and Mann-Whitney U test. The results showed that there was a difference in the improvement of mathematical communication ability between students who used the Think Pair Share learning model and those who used conventional learning. However, there was no difference in the improvement of metacognitive awareness between students who used the Think Pair Share model and those who used conventional learning.